Exploring Student Satisfaction in Learning with Podcast Applications: A Qualitative Study Based on Open-Ended Questions - Permatasari, Indah; Hutabarat, Peny Meliaty; Adelina, Erni (UI Scholars Hub, 2024)
This study aims to explore student satisfaction with the use of podcasts as a learning medium in the Non-News Radio Production course. A qualitative approach was used, with three open-ended questions posed to students: (1) What different experiences did you have when listening to the course material via podcast?(2) Did listening to the course material through podcasts help you focus on understanding the material? And why? And (3) provide your opinion on the Adapto podcast material shared during the Non-News Radio Production course in the 4th semester. The data obtained was thematically analyzed to identify the main emerging themes. The results indicate that students appreciated the flexibility and ease of access provided by the podcasts. Some students felt that podcasts helped them focus better and understand the materials, while others mentioned challenges in maintaining concentration. Feedback on the Adapto podcast content was generally positive, though students also offered suggestions for improvement. These findings suggest that podcasts hold significant potential as an effective learning medium, especially in audio-based courses such as Non-News Radio Production. However, to maximize its benefits, attention should be given to content design and the integration of interactive elements to enhance students’ engagements.